Difficult questions about people and nature Deep Ecology and the preservation of nature - Jaromi, Stanisław (Studia Ecologiae et Bioethicae, 2004)
Today people seem to have endless consumption needs while the world we live in is finite with limited resources. This easily leads to an ecological crisis. Arne Naess and different representatives of the current „deep ecology" ask and explain „ecological wisdom "in an attempt to find a solution for this crisis. This situation considers the basic dispute between the choice of human lifestyles, such as affirming the value of personal wealth, against the best interest of nature and natural resources. It is asked: What are the implications between the growth of consumption and the exploitation of nature? The present article takes up the difficult task of presenting basic ideas of deep ecology in the context of other ecological theories and praxis. It characterizes the dispute between deep ecology and different proposals of preservation of nature and the resolution of the global ecological crisis. Furthermore, it represents a critical analysis of the philosophical basis of deep ecology and points to the Christian/Franciscan attitudes of brotherhood towards our „smaller brothers" - the plants and animals.